2005
DOI: 10.1002/tox.20132
|View full text |Cite
|
Sign up to set email alerts
|

High levels of blood lead in griffon vultures (Gyps fulvus) from Cazorla natural park (southern Spain)

Abstract: The blood lead of 23 griffon vultures (Gyps fulvus) trapped in 2003 was analyzed in order to evaluate exposure to lead in the vulture population of Cazorla Natural Park (in southern Spain). In 2001 the use of leaded gasoline in vehicles was banned in the European Union; however, lead ammunition is still used in Spain in big-game hunting for red deer, fallow deer, mouflon, and wild boar, which are ingested by vultures from September to March. The mean concentration of lead in blood was 43.07 +/- 31.96 microg/dL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 15 publications
(17 reference statements)
2
30
1
2
Order By: Relevance
“…Lead is known to induce a wide range of biochemical and physiological dysfunctions to humans and laboratory animals. Recent epidemiological studies have revealed that increased level of lead in the blood has an association with several disease outcomes such as hypertension, peripheral artery diseases, kidney diseases, neurodegenerative diseases and cognitive impairments [10][11][12]. Lead exposure is also implicated in a broad clinical spectrum of disease, including hematological, renal, cardiovascular, neurological, developmental and behavioral disorders [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lead is known to induce a wide range of biochemical and physiological dysfunctions to humans and laboratory animals. Recent epidemiological studies have revealed that increased level of lead in the blood has an association with several disease outcomes such as hypertension, peripheral artery diseases, kidney diseases, neurodegenerative diseases and cognitive impairments [10][11][12]. Lead exposure is also implicated in a broad clinical spectrum of disease, including hematological, renal, cardiovascular, neurological, developmental and behavioral disorders [13].…”
Section: Introductionmentioning
confidence: 99%
“…Literature reports have also revealed that lead is a toxic heavy metal associated with a number of health problems to individuals exposed to it [6,[10][11][12][13]. However, there was no previous study carried out to understand the levels to which the roadside soils of the eastern towns of Ethiopia; namely, Bishoftu, Modjo, and Adama towns were polluted by lead accumulation originated from the heavy vehicular densities.…”
Section: Introductionmentioning
confidence: 99%
“…Birds ingesting pieces of hunting ammunition are exposed to lead intoxication (see review in Fisher et al 2006;Mateo et al 2007) to the extent that its incidence can be a serious threat to large-scale reintroduction projects such as that of the California condor in North America (Finkenlstein et al (2012 and references therein). Lead levels are also very high in Europe, for instance Iberian griffon vultures show seasonal and spatial variations according to the rate of consumption of wild ungulates (García-Fernández et al 2005). Moreover, carcasses resulting from hunting activities frequently accumulate at a few points at the end of hunting activities (Wilmers et al 2003), which mimics the predictability offered by vulture restaurants and may result in similar negative effects (see above).…”
Section: How Do Vultures Fit Into a Rewilding Continent?mentioning
confidence: 98%
“…The relationship between vultures and wild ungulate hunting has previously only been referred to (e.g. García-Fernández et al 2005;Cade 2007). To our knowledge, the influence that hunting could have in the ecology and conservation of this scavenger guild has not been assessed.…”
Section: Communicated By C Gortázarmentioning
confidence: 99%
“…In the case of the vultures, an exposure to lead from spent ammunition in large game carcasses has been shown and can potentially lead to lead toxicity (García-Fernández et al 2005;Cade 2007;Dobrowolska and Melosik 2008). This lead poisoning may have important effects at both individual and population levels (Gangoso et al 2009).…”
Section: Conservation Implicationsmentioning
confidence: 99%